Urgensi Manajemen Dalam Perspektif Pendidikan Islam - Alfi Maulia Rahma (Prodi PGMI STAI Sabili Bandung, 2022)
Lately, management as a science is so popular that many studies have focused on management in the form of training, seminars, lectures, or the opening of management study programs including economic management, human resource management, education management, and so on. In subsequent developments, management has been implemented in various issues that are spiritual in nature, such as heart management. This research uses library research methods or a collection of literature (material) from various sources, journals, articles and books. The results of the study show that the most important thing in the management of Islamic education is the management components. There are at least 7 (seven) management components that must be managed properly and correctly, including curriculum and teaching programs, educational staff (school personnel/employees), student affairs, finance and financing, educational facilities and infrastructure, school and community collaboration, and service delivery. special educational institutions